2019
DOI: 10.1080/02691728.2019.1587543
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Image of Science in the Business Sector: Surveying and Modeling Scientific Culture, Perception and Attitudes Towards Science

Abstract: Jesús Rey-Rocha graduated in Biology from the Universidad Complutense de Madrid and holds and MsC in Electronic Information Management from the University of Sheffield. He also holds a Doctorate in Sciences from the Universidad Autónoma de Madrid. He is Principal Researcher at the Research Group on Scientific Evaluation and Transfer, Spanish Council for Scientific Research (CSIC). His current research interests center on scientific knowledge communication and transfer, and on scientific culture and perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
2
7
0
1
Order By: Relevance
“…The results reported here confirm the potential we had already anticipated (Rey-Rocha et al, 2019;González-Bravo et al, 2020) of the Public Understanding of Science approach to light up issues related to scientific culture, not only in the general population but also in new scenarios such as the business sector.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The results reported here confirm the potential we had already anticipated (Rey-Rocha et al, 2019;González-Bravo et al, 2020) of the Public Understanding of Science approach to light up issues related to scientific culture, not only in the general population but also in new scenarios such as the business sector.…”
Section: Discussionsupporting
confidence: 83%
“…In general, elites express 'a remarkably lower level of traditionalism', and they are 'more inclined to idealize science' than is the general population (2011). In the same year, López-Navarro et al (2011) also confirmed that, in the Spanish context, the perception of science in the wider public and among entrepreneurs and self-employed workers was significantly different, particularly regarding institutional trust and risk management In a recent work, we found that the image of science in the business sector is shaped by 'entrepreneurs' and business managers' perception of science, their interest in and knowledge of science and technology, and their willingness to take action regarding science, R&D and innovation' (Rey Rocha et al, 2019). We thus propose that business engagement in R&D is related to entrepreneurs' and managers' perception of science.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations